CHRONIC DAILY HEADACHE: MEDICATION OVERUSE AND PSYCHIATRIC MORBIDITY - Ravi, Gupta; Bhatia , Manjeet S; Vishal, Chhabra (Journal of Pakistan Psychiatric Society, 2007)
Objectives: The objectives of the study were: (i) To assess the frequency of different chronic daily headaches in patients using ICHD-2 criteria (ii) To find out the frequency and type of medication overuse and psychiatric morbidity in chronic daily headache subjects. Design: Cross sectional observational study. Place and duration of study: The study was conducted in the psychiatry outpatient department of a teaching medical institution during January to September 2005. Subjects and Methods: Subjects suffering from chronic daily headache were recruited from a specialized headache clinic in a tertiary care hospital’s Psychiatry department. The diagnoses were made according to ICHD-2. Medication overuse was defined according to ICHD-2 criteria and psychiatric illness was diagnosed following ICD-10 criteria in CDH patients. In subjects fulfilling the criteria for ‘medication overuse’, the culprit drug was stopped immediately and prophylactic therapy was started. Results: Frequency of chronic daily headache was 37% in this sample. Females outnumbered males (1: 1.52) and formed higher number of migraine cases (p=0.02). Tension Type Headache (TTH) was most frequent headache (48.5%). According to ICHD-2 criteria, probable medication overuse headache could be diagnosed in all patients, which precluded the diagnosis of chronic migraine and chronic TTH. Psychiatric morbidity was seen in 70.3% subjects and mild to moderate depression was the most common illness (53%). TTH subjects showed predisposition for anxiety disorders (OR= 6.41; p= 0.004). Conclusion: TTH is the most common subtype of CDH when ICHD-2 is followed. Medication overuse is common in this group of patients and these probably should be discontinued according to substance dependence de-addiction model for better compliance, and even more slowly in subjects with chronic migraine headache. Psychiatric morbidity is prevalent in CDH patients and requires special attention. Key words: Chronic Headache, Psychiatric morbidity, Treatment adherence, Analgesic overuse.